A 28V NMOS power switch and bootstrap driver with integrated PA gate driver. (December 2022) - Xu, Honglin; Zhang, Hao; Wu, Junjie
Abstract: For low power dissipation and area reasons, achieving a small size driver circuit for high power amplifiers (HPAs) is critical. Performing high-voltage driving and control technology based on NMOS power transistor is very important to achieve high efficiency. This paper proposes a fully integrated NMOS transistor driving circuit with an integrated on-chip NMOS power LDMOS transistor, and a CMOS gate driver for the HPA is also integrated capable of handling 1 μF capacitor and dozens of mA loads. This strategy ensures that the drain supply of HPA is modulated and gate power supply is supported simultaneously. The bootstrap driver circuit proposed in this work is suitable for continuous wave applications, and has faster response speed and smaller chip area. Measurements from a test chip in 180 nm high voltage BCD technology confirm the proposed strategy achieved in this paper.